Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1149/2.0061603jes
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Behavior of Polyimide Binders in Li and Na Cells

Abstract: The electrochemistry of aromatic and aliphatic polyimide binders was characterized in composite coatings for Li-ion and Na-ion battery negative electrodes. Aromatic polyimide was found to have a large first lithiation capacity of 1943 mAh/g and a reversible capacity of 874 mAh/g in lithium cells. The large first lithiation capacity is suggestive of its full reduction to carbon. Subsequent cycles of aromatic-PI are also similar to that of hydrogen containing carbons. Aromatic-PI is also active in Na cells, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 20 publications
5
40
0
Order By: Relevance
“…LiPAA is not an electrochemically active binder and does not contribute to the reversible or irreversible capacity. 19 As expected, the electrode with PR binder has a greater first lithiation and reversible capacity than the coating with LiPAA binder, since the electrochemically active PR binder contributes to the coating's capacity. Similarly, aro-PI binder has a higher first lithiation and reversible capacity than PR, and, as expected, the coating with aro-PI binder has the highest first lithiation and reversible capacity of all three coatings.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…LiPAA is not an electrochemically active binder and does not contribute to the reversible or irreversible capacity. 19 As expected, the electrode with PR binder has a greater first lithiation and reversible capacity than the coating with LiPAA binder, since the electrochemically active PR binder contributes to the coating's capacity. Similarly, aro-PI binder has a higher first lithiation and reversible capacity than PR, and, as expected, the coating with aro-PI binder has the highest first lithiation and reversible capacity of all three coatings.…”
Section: Resultssupporting
confidence: 57%
“…17,18 Recently, we have shown that aro-PI has a very large first lithiation capacity of 1943 mAh/g, corresponding to a 34 electron reduction process. 19 This reduction capacity is consistent with the charge required to fully decompose the aro-PI to a hydrogen containing carbon. The resulting decomposition products also had similar electrochemical properties as hydrogen containing carbon, with a reversible capacity of 874 mAh/g, leading to added electrode capacity.…”
supporting
confidence: 68%
See 3 more Smart Citations